A Panel of Engineered Ubiquitin Variants Targeting the Family of Domains Found in Ubiquitin Specific Proteases (DUSPs). Issue 24 (3rd December 2021) - Tang, Jason Q.; Veggiani, Gianluca; Singer, Alex; Teyra, Joan; Chung, Jacky; Sidhu, Sachdev S.
Graphical abstract: Highlights: We developed a new phage-displayed UbV library to target DUSPs. The library yielded tight and specific DUSP-binding UbVs. A DUSP-binding UbV inhibited the catalytic activity of USP15, USP11 and USP20 Abstract: Domains found in ubiquitin specific proteases (DUSPs) occur in seven members of the ubiquitin specific protease (USP) family. DUSPs are defined by a distinct structural fold but their functions remain largely unknown, although studies with USP4 suggest that its DUSP enhances deubiquitination activity. We used phage-displayed libraries of ubiquitin variants (UbVs) to derive protein-based tools to target DUSP family members with high affinity and specificity. We designed a UbV library based on insights from the structure of a previously identified UbV bound to the DUSP of USP15. The new library yielded 33 unique UbVs that bound to DUSPs from five different USPs (USP4, USP11, USP15, USP20 and USP33). For each USP, we were able to identify at least one DUSP that bound with high affinity and absolute specificity relative to the other DUSPs. We showed that UbVs targeting the DUSPs of USP15, USP11 and USP20 inhibited the catalytic activity of the enzyme, despite the fact that the DUSP is located outside of the catalytic domain. These findings provide an alternative means of inhibiting USP activity by targeting DUSPs, and this mechanism could be potentially extended other DUSP-containing USPs.